A randomized pilot trial assessing the reduction of gout episodes in hyperuricemic patients by oral administration of Ligilactobacillus salivarius CECT 30632, a strain with the ability to degrade purines - Rodríguez, Juan M.; Garranzo, Marco; Segura, José; Orgaz, Belén; Arroyo, Rebeca; Alba, Claudio; Beltrán, David; Fernández, Leónides (Frontiers in Microbiology, 2023)
Hyperuricemia and gout are receiving an increasing scientific and medical attention because of their relatively high prevalence and their association with relevant co-morbidities. Recently, it has been suggested that gout patients have an altered gut microbiota. In this study, the potential of some Ligilactobacillus salivarius strains to metabolize purine-related metabolites was evaluated. Among them, L. salivarius CECT30632 was the most efficient for inosine (100%), guanosine (100%) and uric acid (50%) conversion and, therefore, it was selected for a pilot clinical trial involving 30 patients with hyperuricemia and a history of recurrent gout episodes. Half of the patients consumed L. salivarius CECT30632 (9 log10 CFU/day; probiotic group; n = 15;) for 6 months while the remaining patients consumed allopurinol (100-300 mg/daily; control group; n = 15) for the same period. In comparison with the control group, administration of the strain resulted in a significant reduction in the number of gout episodes, the use of gout-related drugs and in some blood parameters related to oxidative stress, liver damage or metabolic syndrome.